Influência de características físicas e química dos materiais de abutments de implantes em zircônia e titânio na adesão e viabilidade de células epiteliais gengivaiS OBA-9 - Rigolin, Maria Silvia Mauricio [UNESP] (2014)
Given the need for effective early mucosal barrier around dental implants, the present study evaluated, in vitro, the influence of physical and chemical characteristics of materials simulating abutments implants surfaces in titanium (T) and zirconium (ZrO2) on gingival epithelial cells OBA-9 adhesion. For this study, disks-shaped samples (n=13) of titanium and zirconium were tested, and as positive and negative control groups, bovine enamel disks (BE), and glass coverslips (GCS), respectively. Previously the cellular adhesion surface roughness (Ra), surface free energy (SFE) and the chemical composition of specimens by X-ray Spectrometer Dispersive Energy in Scanning Electron Microscope (SEM) were evaluated. After the periods of cellular adhesion, 1 and 24 hours, the cellular viability was evaluated by MTT Assay (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) and the morphology of the epithelial cells adhered to the surfaces was analyzed using the SEM. The data of cell viability were statistically evaluated by two-way ANOVA (Material and period of analysis), while the SFE data were submitted to Kruskal-Wallis and Mann-Whitney tests, considering a significance level of 5%. The T specimens showed the highest values of SFE (6.2 N/m), followed by ZrO2 (5.8 N/m), GCS (4.9 N/m), and BE (4.7 N/m). It was observed that the factors material (p = 0.336) and periods of analysis (p = 0.400) showed no effect on cell viability data, as well as the interaction between them (material* period of analysis, p = 0.559). The analysis of cell morphology showed that cells adhered to the T and ZrO2 surfaces presented similar spreading, which was higher compared to the BE and GCS surfaces. It was concluded that there was no difference between the cellular adhesion to different materials for implant abutments, T and ZrO2, in evaluated periods. However, cell spreading was qualitatively higher in rougher surfaces and greater titanium and zirconia...